PENDEKATAN ENTERPRISE RISK MANAGEMENT DALAM PEMETAKAN RISIKO DI KOPERASI SIMPAN PINJAM - SUBAGYO -; DIAH AYU SEPTI FAUJI (Jurnal Akademika, 2019)
Giving loans contains risks, one of which is uncollectible accounts. This study aims to: 1) identify the risks faced by Happy cooperatives, 2) measure and map risks, and 3) formulate risk mitigation strategies. The data analysis method used to analyze the data uses the Enterprise Risk Management (ERM) approach, where risk management with ERM can help companies be better prepared to deal with uncertainty, increase added value, and competitive advantage.Risk mapping with the ERM approach is carried out based on eight ERM components. The three components used in this study are internal environment, objective setting, and event identification. These three components are carried out to capture the situation in Happy cooperatives and identify the risks that exist. The results of the study of the Happy cooperative business processes show that there are various strategic, operating, reporting, and compliance risks identified in the stages of the business process. The results showed 1) the risks found in the stages of the Bahagia cooperative business process related to the fields of strategic, operating, reporting, and compliance, 2) the level of risk experienced by the Bahagia cooperative was reflected in the risk map formed on the measurement of risk based on probability and impact. and 3) strategies that need to be developed for effective risk mitigation for happy cooperatives prioritized in handling the highest risks first and then to lower risks.Keywords: Enterprise Risk Management, risk mapping